Controlled fabrication of nickel and cerium mixed nano-oxides supported on carbon nanotubes for glucose monitoring. (1st February 2023) - Waqas, Muhammad; Yang, Linjuan; Wei, Yuhui; Sun, Yue; Yang, Fan; Fan, Youjun; Chen, Wei
Abstract: Carbon nanomaterials-loaded mixed metal oxides are the promising candidates to increase the electrochemical efficacy for glucose monitoring. In this paper, we developed a new hybrid material based on multi-walled carbon nanotubes-supported nickel and cerium mixed oxide nanocomposite (NiCeOx /MWCNTs) through one pot hydrogen co-reduction strategy for non-enzymatic electrochemical glucose sensing. The microscopic and spectroscopic features of as-prepared samples were thorougly characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) techniques. Further, cyclic voltammetry (CV) and chronoamperometry (CA) methods were applied to investigate the electrochemical efficacy of designed electrode towards glucose sensing. The results revealed that, the synergetic effect of nickel and cerium mixed oxides as well as brilliant conductivity of MWCNTs collectively enhanced the electrocatalytic activity of the designed materials for glucose oxidation. Therefore, the fabricated NiCeOx /MWCNTs-based sensor retains the excellent electrochemical efficacy towards glucose sensing as compared to their counterparts including wider linear range (0.007∼0.466 mM and 0.466∼3.44 mM), lower limit of detection (1.8 μM, S/ N = 3), satisfactory sensitivities (271.53 and 429.95 μA mM −1 cm −2 ) as well as good reproducibility, high stability and selectivity. More specifically, the designed NiCeOx /MWCNTs-based sensor offered brilliant real time applicability to precisely monitor glucose level in diluted human serum samples. This study provided an appealing strategy for the development of simple, efficient and cost-effective non-enzymatic electrochemical glucose sensing platform. Graphical abstract: Image, graphical abstract